Integrated Chalcogenide Photonics for Microresonator Soliton Combs. Issue 3 (3rd November 2022) - Xia, Di; Yang, Zelin; Zeng, Pingyang; Zhang, Bin; Wu, Jiayue; Wang, Zifu; Zhao, Jiaxin; Huang, Jianteng; Luo, Liyang; Liu, Dong; Yang, Shuixian; Guo, Hairun; et al.
Abstract: Integrated nonlinear photonics, combined nonlinear optics with state‐of‐the‐art photonic integration, play a crucial role in chip‐integrated technologies including optical frequency combs, molecular spectroscopy, and quantum optics. Optical materials with favorable properties are the foundation to promote integrated photonic devices with bandwidth, efficiency, and flexibility in high‐volume chip‐scale fabrication. In this work, a newly developed chalcogenide glass‐Ge25 Sb10 S65 (GeSbS) is presented for nonlinear photonic integration and for dissipative soliton microcomb generation. The GeSbS features wide transparency (0.5–10 µm), strong nonlinearity (1.3 × 10 −18 m 2 W −1 ), and low thermo‐refractive coefficient (3.1 × 10 −5 K −1 ), and is complementary metal oxide semiconductor (CMOS)‐compatible in fabrication. In this platform, chip‐integrated optical microresonators with an average intrinsic quality ( Q ) factor of ≈1.97 × 10 6 are implemented, and lithographically controlled dispersion engineering is carried out. In particular, both a bright soliton‐based microcomb with bandwidth of 240 nm (≈1440–1680 nm) and a dark‐pulse comb with bandwidth of 80 nm (≈1510–1590 nm) are generated in a single microresonator in its separated fundamental polarized mode families.The ten‐milliwatt level of soliton microcomb operation power facilitates the monolithically integrated photonic circuits. The results provide a potential material platform for integrated nonlinear photonics for highly compact and high‐intensity nonlinear interactions in visible and infrared regions. Abstract : Both a bright soliton‐based microcomb and a dark‐pulse comb are generated on the 10 mW level pumping powers in a same chip‐integrated optical microresonator based on a newly developed chalcogenide glass‐Ge25 Sb10 S65 in its separated fundamental polarized mode families. The results provide a potential material platform for integrated nonlinear photonics for highly compact, high‐intensity nonlinear interactions in visible and infrared regions.